2017
DOI: 10.3390/f8060184
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Laser Scanning for Forest Inventories—Tree Diameter Distribution and Scanner Location Impact on Occlusion

Abstract: Abstract:The rapid development of portable terrestrial laser scanning (TLS) devices in recent years has led to increased attention to their applicability for forest inventories, especially where direct measurements are very expensive or nearly impossible. However, in terms of precision and reproducibility, there are still some pending questions. In this study, we investigate the influence of stand parameters on the TLS-related visibility in forest plots. We derived 2740 stand parameters from Swiss national for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 32 publications
(39 reference statements)
6
78
0
1
Order By: Relevance
“…Note that nominal values are per flight strip and actual point density is computed using all returns, including strip overlap and multiple returns. 22rsfs.royalsocietypublishing.org Interface Focus 8: 20170046 experiment in a temperate mixed forest agree very well with the simulation experiment from Abegg et al[35], who were able to show that TLS suffers from lower sampling density towards the top-of-canopy, which only can be mitigated by a large increase of the number of scans, which might come at prohibitively high costs.On the other hand, having more points does not always mean getting more information. Comparing plot-level canopy profiles of the UAV and traditional ALS data, very high correlations were observed, despite the large difference in point density of about 15 m 22 for ALS and 3200 m 22 for UAVLS…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Note that nominal values are per flight strip and actual point density is computed using all returns, including strip overlap and multiple returns. 22rsfs.royalsocietypublishing.org Interface Focus 8: 20170046 experiment in a temperate mixed forest agree very well with the simulation experiment from Abegg et al[35], who were able to show that TLS suffers from lower sampling density towards the top-of-canopy, which only can be mitigated by a large increase of the number of scans, which might come at prohibitively high costs.On the other hand, having more points does not always mean getting more information. Comparing plot-level canopy profiles of the UAV and traditional ALS data, very high correlations were observed, despite the large difference in point density of about 15 m 22 for ALS and 3200 m 22 for UAVLS…”
supporting
confidence: 85%
“…As Abegg et al [35] showed in their simulation study, the point density above TLS scanners is the lowest when compared with all considered elevation angles and decreases with distance from the scanner. Thus, this under-sampling of the upper canopy is partly system imminent and can only be mitigated by very dense placement of scanner locations, i.e.…”
Section: A Change Of Perspective: Terrestrial Laser Scanners From a Cmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, RS technologies can be used to derive a large range of forest health indicators [6,[15][16][17]. Studies increasingly refer to the importance of combining national forest inventory field plots and RS data for assessing forest health [18,19], but only a limited number of countries [20] and operational programs support plot-based national forest inventories monitoring by using close-range and air and spaceborne RS data.A study on the significance of RS in national forest inventories [20] showed that approximately 71% (32 out of 45 countries) consider their national forest inventory (NFI) to depend on or partly depend on earth observation data. Approximately 31% of those asked (14 countries) found the use of aerial images for NFI to be indispensable.…”
mentioning
confidence: 99%
“…Previous research has reported that the quality and completeness of the point cloud is highly 177 dependent on scanner distance and occlusion (Abegg et al 2017, Pyörälä et al 2018b). Here, we 178 examined to what degree scanner distance and self-occlusion affected branch detection.…”
Section: Errors 176mentioning
confidence: 99%